Comportamiento del nivel de actividad física de acuerdo con el día de la semana en las mujeres posmenopáusicas - Eduardo Rossi, F. [UNESP]; Diniz, T. A. [UNESP]; Buonani, C. [UNESP]; Melo Neves, L. [UNESP]; de Souza Fortaleza, A. C. [UNESP]; Destro Christofaro, D. G.; Forte Freitas Junior, I. (Centro Andaluz de Medicina del Deporte, 2017)
Objective The aim of this study was to compare the differences in the levels of physical activity practiced during the weekdays and weekends in obese postmenopausal women. Method 117 post-menopausal women aged between 50 and 79 were evaluated. To estimate the percentage of body fat the Dual-Energy X-ray Absorptiometry was used. The assessment of physical activity level was obtained using a tri-axial accelerometer. Results There was a significant increase in physical activity-light and a significant decrease in physical activity moderate, vigorous, moderate–vigorous and overall number of counts at the weekend compared to the weekdays. The physical activity moderate–vigorous reduced by an average of 38.6% (p < 0.001) at the weekend compared to the weekdays. Conclusion Obese post-menopausal women presented decreasing physical activity moderate, vigorous, moderate–vigorous and overall number of counts at the weekends compared to the weekdays and an increase in physical activity light.
Comportamento do nível da atividade física de acordo com o dia da semana em mulheres na pós-menopausa
Physical activity level behavior according to the day of the week in postmenopausal women
Keywords: Accelerometry; Climacteric; Motor activity; Obesity; Women